The adaptation process in port governance: The case of the Latin countries in South America and Europe - Fernando González Laxe; Ricardo J. Sánchez; Lorena García Alonso (Journal of Shipping and Trade (JST), 2016)
The particular location of port infrastructure holds characteristics that determine the activity of the port, both with respect to traffic and with respect to implementing competitive strategies; and the efficiency and efficacy of infrastructure depend on the governance systems that regulate the ports. Likewise, the development of port activity echoes in the regional economy as well, hence governance becomes integral to maximizing the impact of ports on their region's economic development. However, the activity of a port transcends the domestic/regional frontiers, as long as the port intends to take part in a global supply chain. Achieving this aim poses a challenge on the authorities that govern port activity, and this challenge needs to be seized when it comes to adjusting the governance to external and internal goals.In the specific case of the analysed ports, the prevailing governance model is known as Landlord, which differs noticeably from port to port. These differences make it possible to distinguish the orientation of European ports from that of the analysed Latin American ports, showing a dissimilar adjustment of the conception of governance that followed objectives that were not simultaneous. The paper draws forth a questioning of the uniqueness of the denomination Landlord and its legitimacy given the new challenges. Furthermore, the paper opens the way to understanding the need to adapt governance to changes, given the examined experiences. The analysis covers the following cases: Argentina, Brazil, Chile, Colombia, France, Italy, Portugal and Spain.
Keywords: 650; Governance; Port system; Ports; Latin America; Europe